2015
DOI: 10.1002/chir.22429
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Method for 2,2'‐Disubstituted Fluorinated Binaphthyl Derivatives and Application as Chiral Source in Design of Chiral Mono‐Phosphoric Acid Catalyst

Abstract: A practical synthetic method for 2,2'-disubstituted fluorinated binaphthyl derivatives was achieved using magnesium bis(2,2,6,6-tetramethylpiperamide) [Mg(TMP)(2)], prepared from LiTMP (2 equiv) and MgBr(2) (1 equiv), which allows for access to a variety of fluorinated binaphthyl compounds. The utility of the fluorinated binaphthyl backbone was evaluated in F10 BINOL derived chiral mono-phosphoric acid (R)- as the chiral Brønsted acid catalyst. The catalyst (R)- performs exceptionally well in the catalytic ena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 60 publications
0
12
0
Order By: Relevance
“…We speculated that enhancing the acidity of the catalytic system would solve the problem. However, the reported strong Brønsted acid catalytic systems for ene reaction, such as List's imidodiphosphate (IDP) Brønsted acids and Terada's F 10 BINOL‐derived chiral phosphoric acids, require complex synthetic routes. More readily available strongly acid catalytic systems were then considered .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We speculated that enhancing the acidity of the catalytic system would solve the problem. However, the reported strong Brønsted acid catalytic systems for ene reaction, such as List's imidodiphosphate (IDP) Brønsted acids and Terada's F 10 BINOL‐derived chiral phosphoric acids, require complex synthetic routes. More readily available strongly acid catalytic systems were then considered .…”
Section: Resultsmentioning
confidence: 99%
“…Second, the catalyst must be capable of overcoming significant steric hindrance for the formation of tetrasubstituted carbon stereocenters. Previously reported Brønsted acid catalytic systems for asymmetric ene reactions are limited to carbonyls and aldimines, leading to the formation of hydroxy or amino tertiary carbon stereocenters. Third, an appropriate chiral environment is required to facilitate the stereo‐inducement process.…”
Section: Introductionmentioning
confidence: 99%
“…In the context of the imino–ene reaction, an N -tosyl-α-iminoester has been used as the chelating and highly electrophilic component in all previous reports of chiral Lewis acid catalysis. Our initial study suggested that the imino–ene reaction proceeds when the benzaldehyde-derived N -Fmoc imine 4 was used as an electrophile (Table , entries 5 and 6) . We expected that relatively stronger chiral Brønsted acids, such as 1a , 1c , and 2a , might generate N -Fmoc aldimines directly from the condensation of the aldehydes and a 9-fluorenylmethyl carbamate (FmocNH 2 ) .…”
Section: Resultsmentioning
confidence: 99%
“…Their electronic and steric alterations lead to notable changes in the chemical yields and the stereoselectivities of reactions involving these catalysts. , Unfortunately, the full potential of perfluorinated aryls has not been exploited in the development of chiral Brønsted acid catalysts . We have previously reported the monophosphoric acids 1a and 2a , which incorporate perfluorinated aryls, as stronger chiral Brønsted acid catalysts than the chiral monophosphoric acid 3 (Figure ). In 1a and 2a , the electron-withdrawing nature of the perfluoroaryl groups leads to higher Brønsted acidity, and 1a is a robust catalyst in the Hosomi–Sakurai reaction of N -acyl imines .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation